A rare cause of persistent hyperparathyroidism. Issue 1 (20th November 2020) - Iconaru, Laura; Spinato, Linda; Duttmann, Ruth; Hambye, Anne‐Sophie; Devriendt, Arnaud; Herchuelz, Maxime; Mathey, Celine; Karmali, Rafik; Bergmann, Pierre
Abstract: In a case of patient with persistent hypercalcemia after parathyroidectomy, different imaging techniques and particularly 18F‐fluorocholine PET/CT are important to localize the adenoma even in a very unusual location. Abstract : In a case of patient with persistent hypercalcemia after parathyroidectomy, different imaging techniques and particularly 18F‐fluorocholine PET/CT are important to localize the adenoma even in a very unusual location.